Studi Dampak Pandemi Covid-19 terhadap Perilaku Belajar, Interaksi Sosial dan Tingkat Spiritual Mahasiswa - I Wayan Darna (Jayapangus Press, 2021)
The study aims to analyze learning behavior, social interaction and spiritual level of UHN I Gusti Bagus Sugriwa students due to the pandemic Covid-19 in order to be able to prepare and do the right things in the era of adapting new habits. This study was quantitative research and used cross-sectional design. Samples that were selected by simple random sampling. Data were collected using online questionnaire. The impact of the covid-19 pandemic for students in college activities is (1)the adjustment of online method, because some areas are constrained by internet signal, quotas, learning platforms, etc. (2) social communication in cyberspace has increased, as a result of not being able to meet face-to-face directly and (3) the spiritual level of students is in the good category. Students have more time to correct themselves to be better, more resilient, and take lessons from what happened